Best proximity point results for g-proximal geraghty mappings - Phakdi Charoensawan (2020)
© 2020 by TJM. All rights reserved. Let (X, d) be a complete metric space endowed with a graph G. We introduce a new type of Geraghty contractions which are G-proximal. Best proximity theorems for these mappings in X are given as well as an example supporting the main result. Moreover, we obtain several consequences which generalize other results in the literature.